Structural properties of silver(I) and mercury(II) complexes of D-lactobionate: Self-assembled coordination polymers - Kim, KM; Song, SC; Lee, SB; Kang, HC; Sohn, YS (AMER CHEMICAL SOC, 1998)
Single crystals of silver(I) and mercury(II) D-lactobionates (LBA) grown from aqueous solutions were subjected to X-ray analysis. Both compounds crystallize in the monoclinic space group C2 (No. 5) with unit cell dimensions a = 29.621(5) Angstrom, b = 7.392(2) Angstrom, c = 7.430(2) Angstrom, and beta = 90.75(2)degrees for Ag[LBA]. H2O and a = 29.084(3) Angstrom, b = 7.4066(11) Angstrom, c = 7.4761(9) Angstrom, and = 90.718(9)degrees for Hg[LBA](2). 2H(2)O, Final solutions of both crystal structures reveal that both sugar acid-metal complexes form novel metal-bridged polysaccharides having similar structures achieved by coordination of alcoholic oxygens O(3) and O(6') in LBA to the metals, although both complexes have different local geometries around metal ions: distorted trigonal bipyramidal for Ag[LBA]. H2O and octahedral for Hg[LBA](2). 2H(2)O. Intermolecular interactions were observed through hydrogen bondings of O(4') in the galactosyl unit with O(5) and O(6) in the gluconic acid moieties of the upper polymeric unit, which is presumed to be an important factor inducing the formation of polymeric structures. In addition, a carbohydrate-carbohydrate interaction was also observed through hydrogen bondings between O(2') and O(3') of neighboring galactosyl units. Silver(I) and mercury(II) complexes lose their polymeric nature in water in different manners: the silver(I) complex is fully dissociated, but the mercury(II) complex exists as a monomeric neutral form.
Keywords: D-ALDURONIC ACIDS; AQUEOUS-SOLUTION; METAL-IONS; SUGAR INTERACTION; ANION